EMMPRIN and its ligand cyclophilin A regulate MT1-MMP, MMP-9 and M-CSF during foam cell formation - Seizer, Peter; Schönberger, Tanja; Schött, Moritz; R. Lang, Michael; Langer, Harald F.; Bigalke, Boris; Krämer, Björn F.; Borst, Oliver; Daub, Karin; Heidenreich, Olaf; Schmidt, Roland; Lindemann, Stephan; et al. (Atherosclerosis, 2010)
Upon coincubation with platelets, CD34+ progenitor cells have the potential to differentiate into foam cells, and thereby may promote the progression of atherosclerosis. The exact mechanism of MMP-regulation during the cellular differentiation process to foam cells is still unclear. Thus, we investigated the role of EMMPRIN (CD147) and its ligand cyclophilin A (CyPA) during foam cell formation originating from both monocytes/macrophages and CD34+ progenitor cells. Differentiation of CD34+ progenitor to foam cells was analyzed in a coculture model of progenitor cells and platelets. While CD34+ cells did not express EMMPRIN or MT1-MMP, mature foam cells strongly expressed EMMPRIN, which was associated with MT1-MMP expression as well as MMP-9. Gene silencing of EMMPRIN by siRNA during the cell differentiation process hindered not only the upregulation of MMPs (MT1-MMP, MMP-9), but also the secretion of the cytokine M-CSF. During the differentiation process CyPA was substantially released into the supernatant. The presence of the CyPA inhibitor NIM811 significantly reduced MMP-9 secretion during the differentiation process. Similar results were obtained using the classical pathway of foam cell formation by coincubating human macrophages with AcLDL. Additionally, the presence of soluble EMMPRIN ligands (CyPA, recombinant EMMPRIN) further enhanced MMP-9 secretion by mature foam cells. Consistently, CyPA and EMMPRIN were found in atherosclerotic plaques of ApoE-deficient mice by immunohistochemistry. EMMPRIN is upregulated during the differentiation process from CD34+ progenitor cells to foam cells, whereas its ligand, CyPA, is released. The CyPA/EMMPRIN activation pathway may play a relevant role in promoting the vulnerability of atherosclerotic plaques.